Study of Employee work motivation at PT Bank Sulselbar Makassar Main Branch - A, M Awaluddin; Astuti, Asti; Darwis, Muhammad; Saleh, Sirajuddin; Baharuddin, Aris (Universitas Negeri Makassar, 2019)
Employee motivation at each company becomes very important, with regard to this , nowadays employees in a every company need to improve work productivity both in quantitiy and quality. This study aim to know the description of the level of work motivation of PT. Bank Sulselbar Makassar Main Branch. This research is a descriptive study designed to describe carefully, clearly and objectively about employee work motivation. Data collection techniques used were observation, documentation, questionnaires, and interviews. The result showed that employee work motivation at PT Sulselbar Makassar main branch can be categorized as good, this can be seen in each indicators, which is in the good category, the awards in the the good category, the challenges in the quite good category, responsibilities in the poor category, developments is in a good category, involvement is in a good category and opportinities in the good category